PENGETAHUAN PENDERITA JERAWAT (ACNE VULGARIS) TENTANG SKINCARE DI RW 013 PERUMAHAN MUSTIKA GRANDE BURANGKENG SETU - Putri Eka Sari; Mega Efrilia Efrilia; Neis Siti Nur Kamilla (Jurnal Farmasi IKIFA, 2023)
A multi-center with 1,755 patients with acne (Acne vulgaris) stated that those who used skincare products or skincare for Acne vulgaris. The purpose of this study was to describe the knowledge of acne sufferers (Acne vulgaris) about Skincare in RW 013 Perumahan Mustika Grande Burangkeng Setu for the period March - April 2022, including knowledge about acne and knowledge about skincare. This study uses a quantitative descriptive method. sampling technique for this research used purposive sampling and 100 respondents were obtained. The sample in this study were residents aged 14-35 years, residents who have experienced and are currently experiencing acne (Acne vulgaris). Data collection’s based on primary data in the form of a questionnaire that has been tested for validity and reliability on 30 respondents. The results showed that the knowledge of residents who have or are experiencing acne (Acne vulgaris) about the factors that cause acne’s poor was at 47%, about acne prevention’s moderate was at 42%, about acne treatment’s good was at 35%. Then, knowledge about the definition and function of skincare is moderate was at 40%, about the types of skincare and how to use it’s moderate was at 43% and about how to choose skincare according to skin type is knowledgeable moderate was at 43%. Based on the results of the study, the knowledge of acne sufferers (Acne vulgaris) about skincare is moderate as much as 46 out of 100 respondents (46%).